Factibilidad económica de los programas de intervención ergonómica de los factores psicosociales, condiciones y organización en el área de agroindustria Espam-MFL - Flores Navarrete, Gema Quinche (2015)
The realization of this research was to determine the economic feasibility for ergonomic intervention programs related to psychosocial factors, conditions and organization, to the same effect a search of literature sources framed to each of these factors considered, leading to the execution of a procedure that allowed to evaluate the socioeconomic impact of these programs, using two of the four stages. The first step was to make a description of the job, categorized the company according to risk levels, problems of Safety and Health of Workers (SHW) in which a check list were identified the causes and consequences of the problems encountered by a matrix, weighted through kendall method to determine the level of agreement among experts. Risk factors perceived by the coordinators and workers were also valorized. Second stage consisted in the development of program improvements that measures according to the problems encountered, the actions for the implementation of the proposed measures were imposed, the corrective actions were classified and proceeded to estimate the cost, it resulting in the feasibility of the proposed improvement plan, which came to the conclusion that this will help improve the quality of life of workers, so it is recommended to apply it in companies with similar characteristics